Initial stage of densification of snow in Mizuho Plateau, Antarctica - Nishimura, Hiroshi; Maeno, Norikazu; Satow, Kazuhide (1983)
P(論文) The initial stage of densification of snow was investigated for four 30-m snow cores drilled in Mizuho Plateau, Antarctica, with special reference to the critical density of 550kg/m^3,and to compactive viscosity. The density-depth relations were considerably different among the four cores, but the depth of the density 550kg/m^3 was noted to increase with the distance from the coast. The result could be explained by a physical dependence of snow densification on temperature and accumulation rate. The compactive viscosity coefficient, η, calculated from the density-pressure curves was expressed by an equation η=η_0 exp (bρ) exp (E/kT), where k and T are respectively Boltzmann's constant and temperature, and η_0=1.20×(10)^<-3>N・s/m^2,b=2.57×(10)^<-2>m^3/kg and E=51.6kJ/mol. A densification model was constructed to estimate the pressure or depth at which the critical density 550kg/m^3 is reached, as a function of temperature and accumulation rate. The model in turn makes it possible to estimate the annual accumulation rate at any observation site from the depth at which the density reaches 550kg/m^3 and the mean annual temperature given by the 10-m depth temperature. departmental bulletin paper